2008
DOI: 10.1111/j.1365-2702.2007.02156.x
|View full text |Cite
|
Sign up to set email alerts
|

Stroke: coping strategies and depression among Chinese caregivers of survivors during hospitalisation

Abstract: Nurses should not only pay attention to stroke survivors but also to their caregivers. To help them adjust well from the stroke consequences and avoid depression, nurses should implement effective interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 43 publications
9
48
1
1
Order By: Relevance
“…The burden is more significant for women because they are the usual and often lone carers of the family (Fuh et al, 1999;King et al, 2001;Qiu, 2008). Studies on Chinese care-givers found that spousal carers had more stress than non-spousal carers (Fuh et al, 1999;King et al, 2001;Qiu, 2008), but there was no gender difference in the prevalence of depression (Fuh et al, 1999;Pang et al, 2002). Further research is required to find out the interaction between gender and marital status in the development of psychological problems, and any differences in their effects between the Chinese and Western cultures.…”
Section: Discussionmentioning
confidence: 99%
“…The burden is more significant for women because they are the usual and often lone carers of the family (Fuh et al, 1999;King et al, 2001;Qiu, 2008). Studies on Chinese care-givers found that spousal carers had more stress than non-spousal carers (Fuh et al, 1999;King et al, 2001;Qiu, 2008), but there was no gender difference in the prevalence of depression (Fuh et al, 1999;Pang et al, 2002). Further research is required to find out the interaction between gender and marital status in the development of psychological problems, and any differences in their effects between the Chinese and Western cultures.…”
Section: Discussionmentioning
confidence: 99%
“…The patients with stroke apoplexy state will result in patients, caregivers and society long-term and serious impact. [10] Many scholars have different definitions of rehabilitation stages after stroke. 1) Acute phase: Refers to the stroke just occurred, usually contains 1 to 2 weeks of hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…Over 5.5 million of these patients will eventually die and over two-thirds of all stroke deaths in the world occur in developing countries [6,7]. The annual incidence of stroke per 100000 people in Western countries is 100 to 300 while in Iran, based on some altered studies, average annual stroke attack rates are between 33 to 372 per 100000 [8].…”
Section: Introductionmentioning
confidence: 99%